Preparation method of rudder core titanium alloy precision casting shell
By applying the surface layer slurry at the concave corners and slits of the rudder core titanium alloy fine castings and drying them at low temperature, combined with the sand spreading method of the automatic sand spreader, the problems of slurry leakage and sand grain bridge of the castings in these parts are solved, and higher quality casting molding and production efficiency are achieved.
Patent Information
- Application Number
- CN202510020717.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-11
AI Technical Summary
During the casting process, rudder core titanium alloy fine castings are prone to problems such as slurry leakage, accumulation, cavitation or sand grain bypass in concave corners and slits, resulting in holes, cracks and stratification of the shell, forming internal slag inclusion defects, and in severe cases, the parts are scrapped.
The control of the surface layer preparation process includes applying the surface layer slurry at the concave corners and slits, and slowly drying through low-temperature drying conditions. Combined with the sand spreading method and control of the automatic sand spreader, we ensure that the sand particles effectively pin the slurry under moderate force, avoiding layering and bridge formation.
It effectively reduces the surface sand and internal slag inclusion problems at the concave corners and slits of the castings, improves the quality and molding integrity of the castings, meets customer processing requirements, and simplifies the production process.
Smart Images

Figure CN119794277A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of titanium alloy precision casting mold shell preparation, and in particular to a method for preparing a rudder core titanium alloy precision casting mold shell. Background Art
[0002] Rudder core titanium alloy precision castings are one of the important parts of aerospace equipment. Their main function is to balance and reduce weight, and they play a vital role in controlling the direction of flight. Rudder core titanium alloy precision castings are casting products commonly encountered in the field of investment casting in the aerospace industry. They belong to Class I B castings, and their dimensional accuracy and surface quality requirements are extremely strict. The structural diagram of rudder core titanium alloy precision castings is shown in the figure below. Figure 1 As shown in the figure, the overall specifications of the part are 600×250×18mm; it is characterized by multiple ribs, with concave and convex double-shaped curved surface structures on the top and bottom of the ribs, and crisscrossed distribution, accounting for 3 / 5 of the total area. The dimensional accuracy of the rib area directly affects the flight accuracy of aerospace equipment, so there are higher requirements for casting ribs. However, in the actual casting process, due to the crisscrossing of the ribs to form many concave corners, the shell pouring and sanding process is prone to slurry leakage, accumulation, cavitation or sand bridging at this position, and it is difficult to dry fully, resulting in holes, cracks and stratification in the shell, thereby forming internal slag defects during casting, which seriously leads to the scrapping of parts.
[0003] Among the existing methods, the shell preparation process for narrow gaps or inner cavity structures is to use a reinforcement layer slurry to spray layer by layer or pour it into shape and dry it at one time after the conventional surface layer is prepared. No additional sand is sprinkled on the reinforcement layer until the shell thickness reaches the requirement or the narrow gap is sealed. However, since there is no sand as a reinforcement skeleton to pin the slurry to strengthen the shell, the shell is not only prone to stratification, but its strength and air permeability are also unsatisfactory. CN101590513A lost foam precision composite casting method includes the following process when making a shell: placing the model in a pre-wetting agent for 2 to 3 seconds and then fishing it out, so that the model is evenly coated with paint, sprinkled with zircon sand, and dried for 4 to 6 hours to obtain a surface layer shell; then dip-coating the transition layer paint, sprinkled with sand, and dried for 8 to 12 hours; using a similar method to make a transition layer shell and a back layer shell; finally sealing the slurry with the back layer paint, and then drying for 14 to 18 hours; roasting at a temperature of 950 to 1050°C and keeping warm for 30 to 60 minutes; pouring the molten metal into the shell to form a casting. Although CN101590513A discloses the sequential preparation of the surface layer, transition layer, and back layer, the casting obtained by pouring the prepared shell still has defects and poor quality. Summary of the invention
[0004] In view of this, the present invention aims to propose a method for preparing a shell of a rudder core titanium alloy precision casting. By controlling the surface layer preparation process, a casting with good appearance in concave corners and slits is obtained to solve the problem of poor quality and easy defects of rudder core castings.
[0005] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0006] A method for preparing a rudder core titanium alloy precision casting shell comprises the following steps:
[0007] Step 1: Prepare the surface slurry, apply 1 to 2 coats of the surface slurry on the concave corners and slits of the wax mold of the rudder core titanium alloy precision casting, and then soak the entire part with the surface slurry after drying;
[0008] Step 2: Sprinkle surface sand: Use an automatic sand spreader to sprinkle the surface sand, and control the height of the sand outlet of the automatic sand spreader to 80~100cm from the shell;
[0009] Step 3: Dry the surface layer;
[0010] Step 4: Prepare transition layer slurry, soak the entire module in the transition layer slurry, and evenly coat the transition layer slurry on the module surface;
[0011] Step 5: Spread transition layer sand;
[0012] Step 6: Drying of transition layer;
[0013] Step 7: Prepare the back layer slurry, soak the entire module with the back layer slurry, rotate the module so that the back layer slurry is evenly coated on the module surface, sprinkle sand and dry;
[0014] Step 8: Repeat step 7 until the shell reaches the thickness required by the process.
[0015] Furthermore, in step 1, the drying conditions are: the temperature is controlled at 20-23°C, the humidity is 60-80%, and the drying time is 6-8h.
[0016] Furthermore, in step 2, the surface sand is 60-80 mesh yttrium oxide sand.
[0017] Furthermore, in step one, 4.5 to 5 parts of yttrium oxide powder and 1 part of surface layer binder are weighed in a weight ratio, stirred fully, and the viscosity value is controlled to be 23 to 25s to prepare a surface layer slurry; in step four, 4.5 to 5 parts of yttrium oxide powder and 1 part of surface layer binder are weighed in a weight ratio, stirred fully, and the viscosity value is controlled to be 20 to 22s to prepare a transition layer slurry.
[0018] Furthermore, the mesh size of the yttrium oxide powder is 300-350 meshes, and the surface layer binder is selected from at least one of yttrium sol and zirconium acetate.
[0019] Furthermore, in step three, the module is placed in a drying room for drying, and the temperature is controlled at 23-25° C., the humidity is 60-80%, and the drying time is 12-24 hours.
[0020] Furthermore, in step five, the transition layer sand is 40-80 mesh yttrium oxide sand.
[0021] Furthermore, in step six, the drying time of the transition layer is extended by 1 to 2 hours compared to the drying time of the surface layer.
[0022] Furthermore, in step seven, 16-30 mesh mullite sand is used to evenly sand the back layer of the entire module.
[0023] Compared with the prior art, the method for preparing the rudder core titanium alloy precision casting shell of the present invention has the following advantages:
[0024] (1) First, the concave corners and slits are coated with surface slurry by brushing, and the temperature, humidity and time are coordinated during drying to perform low-temperature drying and appropriately extend the drying time to slowly dry the concave corners and slits to avoid surface cracks. The concave corners and slits have good appearance and shape. The final rudder core casting is of good quality and can meet the customer's processing requirements.
[0025] (2) Select the surface sand reasonably to avoid the formation of bridges at concave corners.
[0026] (3) Choose a reasonable method for spreading the surface sand and control the sanding force by the sanding height to avoid excessive force that causes sand particles to pierce the surface slurry and cause surface pitting, or insufficient force that fails to play a nailing and strengthening role, resulting in surface delamination and peeling.
[0027] (4) The preparation method is simple to operate and does not involve any complicated technical processes. On-site workers do not need special training and can easily complete it. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0029] Figure 1 This is a schematic diagram of the structure of the titanium alloy parts of the rudder core rib frame described in the present invention. DETAILED DESCRIPTION
[0030] The present invention will be further described below in conjunction with specific embodiments. It should be noted that the data in the following experimental examples are obtained by the inventor through a large number of experiments. Due to space limitations, only a part of them is shown in the specification, and those of ordinary skill in the art can understand and implement the present invention under these data. These embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these changes or modifications also fall within the scope protected by the present application.
[0031] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0032] The present invention will be described in detail below with reference to the accompanying drawings and in conjunction with embodiments.
[0033] Step 1: Prepare the surface slurry, apply 1 to 2 coats of the surface slurry on the concave corners and slits of the rib plate of the rudder core titanium alloy precision casting wax model, and then soak the entire part with the surface slurry after drying.
[0034] Specifically, in step one, first apply 1 to 2 coats of surface slurry to the concave corners and slits of the wax mold ribs with a fine soft brush, and then dry. The drying conditions are: temperature controlled at 20 to 23°C, humidity at 60 to 80%, and drying time of 6 to 8 hours. Since the concave corners and slits are not easily soaked with slurry, the surface slurry is first applied by brushing to ensure that the concave corners and slits are evenly coated with the surface slurry. And through the coordinated control of temperature, humidity and time during drying, low-temperature drying is carried out, and the time is appropriately extended to slowly dry and avoid surface cracks. Then the surface slurry is soaked as a whole, and the module is rotated to control the slurry for not less than 30 seconds until the slurry is evenly coated on the module surface.
[0035] In step 1, the preparation method of the surface layer slurry is: 4.5-5 parts of yttrium oxide powder and 1 part of surface layer binder are weighed by weight, and stirred in a slurry bucket for more than 4 hours, and the viscosity value is controlled to be 23-25s. Furthermore, the mesh number of the yttrium oxide powder is 300-350 mesh, and the surface layer binder is selected from at least one of yttrium sol and zirconium acetate. Furthermore, the mesh number of the yttrium oxide powder is 325 mesh.
[0036] Step 2: Sprinkle surface sand.
[0037] Specifically, in step 2, an automatic sand spreader is used to spread the surface sand, and the height of the sand outlet of the automatic sand spreader is controlled to be 80-100 cm from the shell. The present application uses the sand's own weight to reduce the sand, and controls the force to be 80-100 cm from the shell to reasonably control the sand spraying force. If the force is too large, the sand particles will easily penetrate and damage the surface slurry, and if the force is too small, it will not play an effective pinning role and cannot fix the surface slurry.
[0038] In step 2, the surface sand is 60-80 mesh yttrium oxide sand. The surface sand should not be too large, otherwise it will easily form a bridge at the concave corner.
[0039] Step 3: Dry the surface layer.
[0040] Specifically, in step three, the module is placed in a drying room for drying, and the temperature is controlled at 23-25° C., the humidity is 60-80%, and the drying time is 12-24 hours.
[0041] Step 4: Prepare transition layer slurry, and soak the entire module in the transition layer slurry so that the transition layer slurry is evenly coated on the module surface.
[0042] Specifically, in step 4, the method for preparing the transition layer slurry is as follows: 4.5-5 parts of yttrium oxide powder and 1 part of surface layer binder are weighed by weight and stirred in a slurry bucket for more than 4 hours, and the viscosity is controlled to be 20-22 seconds. The viscosity of the transition layer slurry is lower than that of the surface layer slurry, so that the transition layer slurry can more easily penetrate into the surface layer that has been dried and hardened, and fill the gaps in the surface layer. In addition, the transition layer slurry can also play a role in bonding the surface layer and the back layer to ensure the strength of the shell.
[0043] Furthermore, the mesh size of the yttrium oxide powder used in the transition layer slurry is 300-350 meshes, and the surface layer binder is at least one selected from yttrium sol and zirconium acetate.
[0044] Step 5: Sprinkle transition layer of sand.
[0045] Specifically, in step five, the transition layer sand is made of 40-80 mesh yttrium oxide sand, the particle size of the transition layer sand is coarser than the surface layer sand, and angular sand particles are selected, and the nailing slurry increases the interlayer bonding strength.
[0046] Step 6: Let the transition layer dry.
[0047] Specifically, in step six, the module is placed in a drying room for drying, and the temperature is controlled at 23-25°C, the humidity is 60-80%, and the drying time is 12-26 hours. Furthermore, the drying time of the transition layer is extended by 1-2 hours compared to the drying time of the surface layer. Considering that part of the transition layer slurry will penetrate into the surface layer and cause the surface layer to absorb moisture, the drying time of this step needs to be extended.
[0048] Step 7: Prepare the back layer slurry, soak the entire module with the back layer slurry, rotate the module to make the back layer slurry evenly coated on the module surface, sprinkle sand and dry.
[0049] Specifically, in step 7, 1.4-1.5 parts of mullite powder and 1 part of back layer binder are weighed by weight and stirred in a slurry bucket for more than 4 hours. The mesh number of the mullite powder used in the back layer slurry is 150-220 mesh, and the back layer binder is 30% silica sol.
[0050] In step 7, use 16-30 mesh mullite sand to evenly sand the entire module. When drying, put the module into the drying room and control the temperature to 24±2℃ for 6-10 hours.
[0051] Step 8: Repeat step 7 until the shell reaches the thickness required by the process.
[0052] The method for preparing the shell of the titanium alloy precision casting of the rudder core of the present invention can reduce the repeated non-destructive testing, repair welding, annealing and other processes caused by the problems of sand sticking on the surface or internal slag inclusions in the concave corners, slits and other parts of the casting by controlling the shell surface process, greatly reducing the rework cost and shortening the casting production cycle. The concave corners and slits have good appearance, and the rudder core casting finally prepared is of good quality and can meet the processing requirements of customers. Since the preparation method is simple to operate and does not contain complex technical processes, on-site workers do not need special training and can easily complete it.
[0053] It should be noted that in the steps of spreading transition layer sand and back layer sand, due to the existence of the surface layer, the transition layer sand and back layer sand are not easy to damage the surface layer and react with the titanium alloy, so there is no need to specially control the sand spreading force. Example 1
[0054] Prepare the surface slurry: weigh 4.5 parts of 325-mesh yttrium oxide powder and 1 part of yttrium sol according to the weight ratio, place them in a slurry barrel and stir them thoroughly for more than 4 hours, and control the viscosity value to 23s.
[0055] Use a fine soft brush to carefully apply two layers of surface slurry to the concave corners and slits of the wax mold ribs and dry them. The drying conditions are: temperature 20℃, humidity 60%, and drying time 8h. Then, soak the entire surface slurry, rotate the module and control the slurry for no less than 30s, until the surface slurry is evenly coated on the surface of the module.
[0056] The surface sand is spread by an automatic sand spreader, and the height of the sand outlet of the automatic sand spreader from the mold shell is controlled to be 80 cm. The surface sand is 60-80 mesh yttrium oxide sand.
[0057] Place the module in a drying room for drying, and control the temperature to 23°C, the humidity to 60-80%, and the drying time to 24 hours.
[0058] Prepare transition layer slurry: weigh 4.5 parts of 325 mesh yttrium oxide powder and 1 part of yttrium sol in a slurry bucket and stir them thoroughly for more than 4 hours, and control the viscosity value to 20s. Pour the transition layer slurry on the entire module to evenly coat the module surface.
[0059] Use 40~80 mesh yttrium oxide sand to spread the transition layer sand.
[0060] Place the module in a drying room for drying, and control the temperature to 25°C, the humidity to 60-80%, and the drying time to 25 hours.
[0061] Prepare the backing slurry: weigh 1.5 parts of 150 mesh mullite powder and 1 part of 30% silica sol by weight and stir them in a slurry bucket for more than 4 hours. Pour the backing slurry on the entire module and rotate the module to evenly coat the backing slurry on the module surface. Use 16-30 mesh mullite sand to evenly sand the entire module. After sanding, put the module into the drying room and control the temperature to 24±2℃ for 6 hours. Repeat this step until the shell reaches the thickness required by the process. Example 2
[0062] Prepare the surface slurry: weigh 5 parts of 350-mesh yttrium oxide powder and 1 part of zirconium acetate according to the weight ratio, place them in a slurry bucket and stir them thoroughly for more than 4 hours, and control the viscosity value to 25s.
[0063] Use a fine soft brush to carefully apply two layers of topcoat slurry to the concave corners and slits of the wax mold ribs and dry them. The drying conditions are: temperature 23°C, humidity 80%, and drying time 6 hours. Then, soak the entire surface slurry, rotate the module and control the slurry for no less than 30 seconds until the slurry is evenly coated on the surface of the module.
[0064] The surface layer of sand is spread by an automatic sand spreader, and the height of the sand outlet of the automatic sand spreader from the mold shell is controlled to be 100 cm. The surface layer of sand is 60-80 mesh yttrium oxide sand.
[0065] Place the module in a drying room for drying, and control the temperature to 25°C, the humidity to 60-80%, and the drying time to 12 hours.
[0066] Prepare transition layer slurry: weigh 5 parts of 300 mesh yttrium oxide powder and 1 part of zirconium acetate in a slurry bucket and stir them thoroughly for more than 4 hours, and control the viscosity value to 22s. The entire module is soaked in the transition layer slurry so that the transition layer slurry is evenly coated on the module surface.
[0067] Use 40~80 mesh yttrium oxide sand to spread the transition layer sand.
[0068] Place the module in a drying room for drying, and control the temperature to 23°C, the humidity to 60-80%, and the drying time to 14 hours.
[0069] Prepare the backing slurry: weigh 1.4 parts of 220 mesh mullite powder and 1 part of 30% silica sol by weight and stir them in a slurry bucket for more than 4 hours. Pour the backing slurry on the entire module and rotate the module to evenly coat the backing slurry on the module surface. Use 16-30 mesh mullite sand to evenly sand the entire module. After sanding, put the module into the drying room and control the temperature to 24±2℃ for 10 hours. Repeat this step until the shell reaches the thickness required by the process.
[0070] Comparative Example 1
[0071] The preparation method of Comparative Example 1 is the same as that of Example 1, except that manual sanding is performed after the surface layer slurry is poured.
[0072] Comparative Example 2
[0073] The preparation method of Comparative Example 2 is the same as that of Example 1, except that 100-mesh yttrium oxide sand is used when spreading the surface sand.
[0074] Comparative Example 3
[0075] The preparation method of Comparative Example 3 is the same as that of Example 1, except that when preparing the transition layer slurry, the viscosity of the transition layer slurry is controlled to be 28s.
[0076] The shells prepared in Examples 1-2 and Comparative Examples 1-3 were cast separately under the condition of unchanged casting process, 4 groups in one furnace, 2 pieces in one group, 4 furnaces were cast to obtain castings. The castings obtained in Examples 1-2 have complete forming at the concave corners and slits in the rudder core rib plate area, good surface quality, no common casting defects such as titanium beads, collapsed pits, peeling, sand holes, flying burrs and slag inclusions, and the yield rate reached 100%. However, the castings obtained by the method of Comparative Example 1 have collapsed pits and sand holes in the concave corners and slits in the rudder core rib plate area because the force was not reasonably controlled when spreading the surface sand. The castings obtained by the method of Comparative Example 2 also have defects in the concave corners and slits in the rudder core rib plate area, and the molding is poor. The casting obtained by the method of comparative example 3 has peeling at the concave corners and slits in the rudder core rib area. The possible reason is that the viscosity of the transition layer slurry is higher than that of the surface layer slurry, which makes it difficult for the transition layer slurry to penetrate into the dry and hardened surface layer, and it is impossible to fill the missing parts of the surface layer, which is not conducive to the yield rate.
[0077] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.
Claims
1. A method for preparing a rudder core titanium alloy precision casting shell, characterized in that: The steps include: Step 1: Prepare the surface slurry, apply 1 to 2 coats of the surface slurry on the concave corners and slits of the wax mold of the rudder core titanium alloy precision casting, and then soak the entire part with the surface slurry after drying; Step 2: Sprinkle surface sand: Use an automatic sand spreader to sprinkle the surface sand, and control the height of the sand outlet of the automatic sand spreader to 80~100cm from the shell; Step 3: Dry the surface layer; Step 4: Prepare transition layer slurry, soak the entire module in the transition layer slurry, and evenly coat the transition layer slurry on the module surface; Step 5: Spread transition layer sand; Step 6: Drying of transition layer; Step 7: Prepare the back layer slurry, soak the entire module with the back layer slurry, rotate the module so that the back layer slurry is evenly coated on the module surface, sprinkle sand and dry; Step 8: Repeat step 7 until the shell reaches the thickness required by the process.
2. The method for preparing a rudder core titanium alloy precision casting shell according to claim 1, characterized in that: In step 1, the drying conditions are: temperature controlled at 20~23°C, humidity at 60~80%, and drying time at 6~8h.
3. The method for preparing a rudder core titanium alloy precision casting shell according to claim 1, characterized in that: In step 2, the surface sand is 60-80 mesh yttrium oxide sand.
4. The method for preparing a rudder core titanium alloy precision casting shell according to claim 1, characterized in that: In step one, 4.5 to 5 parts of yttrium oxide powder and 1 part of surface layer binder are weighed in a weight ratio, stirred fully, and the viscosity is controlled to be 23 to 25s to prepare a surface layer slurry; in step four, 4.5 to 5 parts of yttrium oxide powder and 1 part of surface layer binder are weighed in a weight ratio, stirred fully, and the viscosity is controlled to be 20 to 22s to prepare a transition layer slurry.
5. The method for preparing a rudder core titanium alloy precision casting shell according to claim 4, characterized in that: The mesh size of the yttrium oxide powder is 300-350 meshes, and the surface layer binder is selected from at least one of yttrium sol and zirconium acetate.
6. The method for preparing a rudder core titanium alloy precision casting shell according to claim 1, characterized in that: In step three, the module is placed in a drying room for drying, and the temperature is controlled at 23-25°C, the humidity is 60-80%, and the drying time is 12-24 hours.
7. The method for preparing a rudder core titanium alloy precision casting shell according to claim 1, characterized in that: In step 5, the transition layer sand is 40-80 mesh yttrium oxide sand.
8. The method for preparing a rudder core titanium alloy precision casting shell according to claim 1, characterized in that: In step six, the drying time of the transition layer is extended by 1 to 2 hours compared to the drying time of the surface layer.
9. The method for preparing a rudder core titanium alloy precision casting shell according to claim 1, characterized in that: In step seven, use 16-30 mesh mullite sand to evenly sand the back layer of the entire module.
Citation Information
Patent Citations
Method for evaporative pattern precise composite casting
CN101590513A
Cited By
Preparation method of high-surface-quality titanium alloy investment precision casting shell
CN120325898A